Cardiovascular Autonomic Dysfunction in Mild and Advanced Parkinson’s Disease - Kim, Joong-Seok (J Mov Disord, 2016)
OBJECTIVE: The purpose of the present study was to investigate cardiovascular autonomic dysfunction in patients with Parkinson’s disease (PD) with mild to severe stages of motor symptoms and to compare cardiovascular autonomic dysfunction between drug-naïve and dopaminergic drug-treated groups. METHODS: This study included 188 PD patients and 25 age-matched healthy controls who underwent head-up tilt-testing, 24-h ambulatory blood pressure (BP) monitoring and 24-h Holter monitoring. Autonomic function test results were evaluated among groups categorized by motor symptom severities (mild vs. moderate vs. severe) and treatment (drug-naïve or dopaminergic drug treatment). RESULTS: Orthostatic hypotension and supine hypertension were more frequent in patients with PD than in healthy controls. The frequencies of orthostatic hypotension, supine hypertension, nocturnal hypertension and non-dipping were not different among groups. Additionally, no significant differences were detected in supine BP, orthostatic BP change, nighttime BP, nocturnal BP dipping, or heart rate variabilities among groups. CONCLUSIONS: Cardiovascular autonomic dysfunction is not confined to moderate to severe PD patients, and starts early in the course of the disease in a high proportion of PD patients. In addition, dopaminergic drug treatments do not affect cardiovascular autonomic function.